Firefighter occupation is associated with increased risk for laryngeal and hypopharyngeal squamous cell carcinoma among men from the Greater Boston area. (27th February 2020) - Langevin, Scott M; Eliot, Melissa; Butler, Rondi A; McClean, Michael; Kelsey, Karl T
Abstract : Objective: Firefighters are exposed to a wide variety of carcinogens during the line of duty, including several associated with head and neck cancer. Existing studies assessing head and neck cancer risk with firefighting have predominately included occupational cohorts or registry data, which are limited by inability to adjust for smoking and alcohol consumption—major risk factors for head and neck cancer. Our objective was to assess the risk of head and neck cancer among men with an occupational history as a firefighter. Methods: This work was conducted using male subjects from a large population-based case–control study of head and neck cancer from the greater Boston area using self-reported occupational history (718 cases and 905 controls). Results: An occupational history as a firefighter was reported for 11 cases and 14 controls. Although no significant association was observed overall, we observed substantial increased risk for hypopharyngeal and laryngeal squamous cell carcinoma among professional municipal firefighters who had a light or no smoking history (OR=8.06, 95% CI 1.74 to 37.41), with significantly increasing risk per decade as a firefighter (OR=2.10, 95% CI 1.06 to 4.14). Conclusion: Professional municipal firefighters may be at increased risk for hypopharyngeal and laryngeal squamous cell carcinoma due to carcinogenic exposures encountered during the line of duty.